Relationship among demographic variables and pupils’ reasoning ability (2008)
Introduction: Pupils reasoning ability is a sine-qua-non to the evaluation of their performance in learning and an indicator of their potential predictors of future performance. Method: The study examined the relationship among demographic variables and reasoning ability of primary school pupils. It drew four hundred pupils from ten (10) purposefully selected public primary schools in Ibadan, Nigeria. The age of these pupils ranged from 9-11 years. A Reasoning Assessment Test developed by (Sokan, 1998) with r = 0.89 cronbach alpha was used for the collection of data. Two hypotheses were developed to guide the study. These were analysed using Pearson Multiple Correlation Matrix and Multiple Regression statistical methods. Results: The results indicate that demographic variables like age, class, and gender correlates positively with pupils reasoning ability and that these three variables significantly predict pupils reasoning ability better than other variables. Discussion and Conclusion: Based on these findings teachers and parents are called upon to see to it that they start stimulation of the children thinking at an early age as soon as they enter school through provision fascinating toys, computers and simulation games.